Critical Flicker Fusion Frequency: A Marker of Cerebral Arousal During Modified Gravitational Conditions Related to Parabolic Flights - Balestra, Costantino; Machado, Marie-Laure; Theunissen, Sigrid; Balestra, Ambre; Cialoni, Danilo; Clot, Christian; Besnard, Stépane; Kammacher, Laura; Delzenne, Julie; Germonpré, Peter; Lafère, Pierre (Frontiers in Physiology, 2018)
In-situ evaluation of human brain performance and arousal remains challenging during operational circumstances, hence the need for a rapid, reliable and reproducible tool. Here we hypothesized that the Critical flicker fusion frequency (CFFF) reflecting/requiring visual integration, visuo-motor skills and decision-taking process might be a powerful, fast and simple tool in modified gravity environments. Therefore 11 male healthy volunteers were assessed for higher cognitive functions with CFFF during parabolic flights. They were assessed at different time points: upon arrival to the base, 30 minutes after subcutaneous scopolamine administration, before parabolas, during hypergravity and microgravity at break time (between the 16th and the 17th parabola), on the return flight and on the ground after landing. First, a stable, and consistent measurement of CFFF could be obtained within 12 seconds. Second, under modified gravitational conditions, the perceptual ability of participants is significantly modified. Compared to the baseline, evolution is characterized by a significant increase of CFFF when in microgravity (0g: 106.9±5.5%), and a significant decrease of CFFF while in hypergravity (2g: 94.5±3.8%). Other time-points were not statistically different from the baseline value. Although the underlying mechanism is still debated, we suggest that the CFFF test is a global marker of cerebral arousal as the result of visuo-motor and decision taking testing based on a simple visual stimulus with an uncomplicated set up that could be used under various environmental conditions. The authors express an opinion that it would be advisable to introduce CFFF measurement during spaceflights as it allows individual longitudinal assessment of individual ability even under conditions of incomplete physiological compensation, as shown here during parabolic flights.